FILSAFAT ETIKA IBNU MISKAWAIH - Ahmad Yunus; Samsul Ma’arif; Hafiz Muhammad Amin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
Ibn Maskawih defines the soul as a simple substance that cannot be sensed by any of the senses. the soul comes from an abundance of active reason ('aql fa'al). The human soul has three levels of power. From a low level, the order is stated as: Al-Nafs al-Bahimiyah (animal lust) which is bad, Al Nafs al-Sabu'iah (lust for wild animals) is moderate, Al Nafs al-Nathiqah (intelligent soul) is good. The soul cannot be accidental because it - in itself - has the power to distinguish between accident and essential concepts, and is not limited to conscious awareness of accidental things by the senses, but can perceive a wide variety of immaterial and abstract entities. Ibn Miskawaih argues that the effort to achieve al- sa'adat cannot be done alone, but must be together on the basis of mutual help and complementarity. The concept of morals developed by Ibn Miskawaih is closer to being said as religious- philosophical ethics, because the thoughts he conveys are always based on the guidance of religious teachings. So it is not uncommon when in his writings found various verses of the Koran and Hadith to support his argument.